An ILP Formulation for the Task Graph Scheduling Problem Tailored to Bi-Dimensional Reconfigurable Architectures. (17th November 2009) - Redaelli, F.; Santambrogio, M. D.; Ogrenci Memik, S.
Abstract : This work proposes an exact ILP formulation for the task scheduling problem on a 2D dynamically and partially reconfigurable architecture. Our approach takes physical constraints of the target device that is relevant for reconfiguration into account. Specifically, we consider the limited number of reconfigurators, which are used to reconfigure the device. This work also proposes a reconfiguration-aware heuristic scheduler, which exploits configuration prefetching, module reuse, and antifragmentation techniques. We experimented with a system employing two reconfigurators. This work also extends the ILP formulation for a HW/SW Codesign scenario. A heuristic scheduler for this extension has been developed too. These systems can be easily implemented using standard FPGAs. Our approach is able to improve the schedule quality by 8.76% on average (22.22% in the best case). Furthermore, our heuristic scheduler obtains the optimal schedule length in 60% of the considered cases. Our extended analysis demonstrated that HW/SW codesign can indeed lead to significantly better results. Our experiments show that by using our proposed HW/SW codesign method, the schedule length of applications can be reduced by a factor of 2 in the best case.